2018
DOI: 10.1016/j.jtcvs.2018.05.057
|View full text |Cite
|
Sign up to set email alerts
|

Mini-Stern Trial: A randomized trial comparing mini-sternotomy to full median sternotomy for aortic valve replacement

Abstract: Compared with FS for AVR, MS did not result in shorter hospital stay, faster recovery, or improved survival and was not cost-effective. The MS approach is not superior to FS for performing AVR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 19 publications
1
61
0
Order By: Relevance
“…The Mini-Stern trial randomised 222 patients to either a fourth space J sternotomy MIAVR or a conventional sternotomy 32. The primary outcome was to determine a difference in postoperative length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…The Mini-Stern trial randomised 222 patients to either a fourth space J sternotomy MIAVR or a conventional sternotomy 32. The primary outcome was to determine a difference in postoperative length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid deployment and sutureless bioprosthetic aortic valves have also helped to facilitate the RAMT approach 8,9 . Recently, enthusiasm for minimally invasive AVR has been tempered by the results of the randomized controlled Mini‐Stern trial, which found no outcome advantage with minimally invasive AVR 10 . Importantly, this study did not include any patients that had a sternum‐sparing RAMT‐AVR 10 .…”
Section: Discussionmentioning
confidence: 99%
“…1 Interestingly, a recent randomized trial by Nair and colleagues 2 demonstrated no apparent clinical benefits with minimally invasive SAVR at the expense of increased costs. The results of that study and Fedak's recent editorial 3 have fueled further debate as to whether there is any advantage to minimally invasive techniques at all.…”
Section: Patient-reported Outcomes: How To Advance the Minimally Invamentioning
confidence: 93%
“…2 In an effort to settle this debate, Nair and colleagues 3 presented results of the Mini-Stern Trial in the December 2018 issue of the Journal. In a study of 222 patients randomly allocated across 2 sites in the United Kingdom, Nair and colleagues 3 found that aortic valve replacement through an upper ministernotomy (MS) did not result in shorter stay, faster recovery, or improved survival relative to full sternotomy. MS was also associated with an increased cost of £1714 per patient, which appeared largely driven by increased perioperative expenses.…”
Section: Patient-reported Outcomes: How To Advance the Minimally Invamentioning
confidence: 99%